Diversidade de fungos micorrízicos em diferentes sistemas de manejo do solo no Bioma Cerrado, MS - SOUZA OLIVEIRA, Anderson,; COÊLHO, Roseline da Silva,; SCHIAVO, Jolimar Antonio, (ANAIS DO ENIC, 2024)
-